The Portrayal of Refugees in the UK Online Press - Leopoldová, Sabina (Univerzita Pardubice, 2018)
This paper deals with the ways in which the British online media depict refugees. This work introduces the discipline of critical discourse analysis and focuses close attention to ideologies. In the analytical part, the thesis examines noun phrases used for a reference to refugees.
Vyobrazení uprchlíků v britském internetovém tisku
Keywords: noun phrases; news reports; critical discourse analysis; ideology; refugees; nominální fráze; novinové zprávy; kritická analýza diskurzu; ideologie; uprchlíci